Effect of Suction Cycles and Suction Gradients on the Water Retention Properties of a Hard Clay - Liufeng Chen; Hua Peng (Advances in Materials Science and Engineering)
The effect of suction cycles and suction gradients on a hard clay is investigated. The cylindrical samples of the hard clay are prepared to carry out the hydration and dehydration tests with different suction gradient and suction cycles. The results show that the suction gradient has little effect on the suction-water content relation, while the suction cycle has great effect on it, particularly the first cycle of hydration and dehydration. The apparent moisture diffusion coefficient of the hard clay has been identified by the use of a two-dimensional diffusion model. The moisture diffusion coefficient varies between 4.10−11 m2/s and 2.10−10 m2/s and it decreases during dehydration while the relative humidity is less than 85%. The results also show that the suction cycles play little effect on the moisture diffusion coefficient.